Recognizing Total Anomalous Pulmonary Venous Drainage (TAPVD) from Natural History to the Supportive Imaging Modalities - Caesario, Fahreza; Swastika Putri, Valerinna Yogibuana (Universitas Brawijaya, 2024)
Congenital Heart Disease (CHD) prevalence was 8 until 9 for each thousand live births, and among all of the CHD, there is only one condition that involved the malformation of the venous system that called Total Anomalous Pulmonary Venous Drainage (TAPVD). TAPVD can be found and yet to be diagnosed in all ages, not only in the childhood era. Adult individuals with TAPVD are susceptible to being misdiagnosed as having a significant secundum atrial septal defect if the condition is not known or suspected. A systematic history taking, physical examination, and another supportive imaging modalities is needed to ensure this structural anomaly.